Rancang Bangun Sistem Navigasi Kekeringan dan Meluapnya Air pada Lahan Berbasis web di BALITKLIMAT - Yoridho, Daffa Damas; Adi, Setyono Hari; Siskandar, Ridwan (Jurnal Sains Indonesia, 2020)
The tight level of global competition in the agricultural sector requires optimal use of climate and water resources. For this reason, a tool is needed to monitor the water level and soil moisture in the land as well as automatic door control on the land in order to make it easier for users to maintain their land. Drought and Water Overflow Navigation System Design on Web-Based Land in BALITKLIMAT is made using acrylic material and has a width of 40 x 40 cm and each side with a height of 15 cm. Navigation System Design for Drought and Water Overflow in Web-Based Land at BALITKLIMAT using LM393 soil moisture sensor and HC-SR04 ultrasonic sensor as water level meter based on NodeMCU microcontroller with automatic door drive output using MG-996 servo motor and monitoring which can be seen on the RBSNKSMAPL website page.